2004
DOI: 10.1021/la030198b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Deposition Processes and Spatial Structures of Alkanethiol and Arylthiol Molecules Adsorbed on Pt(111) Electrodes with in Situ Scanning Tunneling Microscopy

Abstract: In situ scanning tunneling microscopy (STM) was used to examine the spatial structures of n-alkane thiols (1-hexanethiol, 1-nonanethiol, and 1-octahexanethiol) and arylthiols (benzenethiol and 4-hydroxybenzenethiol) adsorbed on well-ordered Pt111 electrodes in 0.1 M HClO4. The electrochemical potential and molecular flux were found to be the dominant factors in determining the growth mechanisms, final coverages, and spatial structures of these organic adlayers. Depending on the concentrations of the thiols, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 47 publications
8
63
0
Order By: Relevance
“…This was the only ordered structure seen on Pt(1 0 0) at h 6 0.5, as nucleation seeds observed at the initial stage of adsorption also contained this ( p 2 · p 2)R45°structure. This result is similar to the observation of benzenethiol admolecules arranged in p(2 · 2) on nucleation seeds on Pt(1 1 1) [20].…”
Section: In Situ Stm Imaging Of Pt(1 0 0) In Benzenethiolcontaining Hsupporting
confidence: 90%
See 1 more Smart Citation
“…This was the only ordered structure seen on Pt(1 0 0) at h 6 0.5, as nucleation seeds observed at the initial stage of adsorption also contained this ( p 2 · p 2)R45°structure. This result is similar to the observation of benzenethiol admolecules arranged in p(2 · 2) on nucleation seeds on Pt(1 1 1) [20].…”
Section: In Situ Stm Imaging Of Pt(1 0 0) In Benzenethiolcontaining Hsupporting
confidence: 90%
“…We recall our previous STM study of benzenethiol molecules adsorbed on Pt(1 1 1), where p(2 · 2) and ( p 3 · p 3)R30°structures are also identified, as those found for sulfur adatoms [20]. Two nearest neighbor molecules are 0.56 and 0.48 nm apart in these two structures, which are less than the van der Waals diameter of a benzene molecule.…”
Section: Introductionmentioning
confidence: 60%
“…8 A recent scanning tunneling microscopy (STM) study reported a high-coverage phase for alkanethiols on Pt(111) with a ( 3 × 3)R30°structure that corresponds to a 5.1 × 10 14 cm -2 coverage. 49 These literature coverage values are thus somewhere between the XPS-determined coverages for SAMs on p-Pt and TS-Pt.…”
Section: Monolayer Thickness Stoichiometry and Molecularmentioning
confidence: 98%
“…75,76 Similarly, a recent STM study provided evidence of local ( 3 × 3)R30°ordering for alkanethiols on single-crystal Pt(111), but also reported difficulties with imaging any long-range ordering. 49 The presence of a disordered component such as S2 could naturally account for these observations.…”
Section: Assignment Of S 2pmentioning
confidence: 99%
“…(1)) Au nþm þ m RSH ! Au n ðAu-S-RÞ m þ mH þ þ me À ð1Þ has been invoked for spontaneous self-assembly [8,9] and for the electrochemically assisted formation of thiol SAMs on Au [10,11] and Pt [12]. (For the former case dioxygen or adventitious impurities serve as oxidant; for the latter, the oxidation is electrochemical).…”
Section: Introductionmentioning
confidence: 99%